Synthesis, Crystal Structures, Antimicrobial Activity, and Acute Toxicity Evaluation of Chiral Zn(II) Schiff Base Complexes - Daniela Gutiérrez Arguelles; Claudia P. Villamizar; Eduardo Brambila-Colombres; Bertin Anzaldo; Angel Mendoza; Guadalupe Hernández Téllez; Pankaj Sharma (Molecules)
Four mononuclear bioefficient zinc coordination complexes [Zn(NN)3](ClO4)2 (A–D) involving chiral bidentate Schiff base ligands have been synthesized and characterized by IR, 1H, and 13C NMR spectroscopy and mass spectrometry. X-ray crystal structures of three of the zinc complexes revealed that the zinc metal ion is hexacoordinated, exhibiting a distorted octahedral geometry where both the nitrogen atoms (NN = pyridyl and imine) of imines are coordinated to the central zinc ion. The isolated zinc complexes were evaluated for their antimicrobial activity in vitro against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, displaying varying levels of growth inhibition. An acute toxicity test conducted using Artemia salina and Swiss albino mice showed that the zinc complexes A–D were non-toxic towards A. salina at concentrations below 414, 564, 350, and 385 µM, respectively, and did not affect liver biochemical parameters, although pyknosis was induced in hepatocytes of the treated mice.